Effect of Soaking of NaCl Solution on Reduction of Calcium Oxalate and Size of Amylum on Purple Yam (Dioscorea alata L.) - Rofi'ana Rofi'ana; Sri Widodo Agung Suedy; Sarjana Parman (NICHE Journal of Tropical Biology, 2018)
Purple yam (Dioscorea alata L.) is a traditional food as a source of alternative carbohydrates and potentially as food functional ingredients. Purple yam contains high carbohydrate and some antioxidant compounds but contains high enough Ca oxalate. This study aims to reduce the content of Ca oxalate by soaking in NaCl solution and analyze its effect on amylum size in purple yam. The research used Completely Randomized Design (CRD) with the single factor of NaCl concentration. Treatment of soaking with different concentrations of 5%, 10%, 15% and with four replications for each treatment. The parameters observed were number and size of crystal Ca oxalate (μm), Ca oxalate content (ppm) and decrease percentage, and amylum size (μm). The data were analyzed using Analysis of Variance (ANOVA) at 95% confidence level and continued by multiple-range test Duncan's Multiple Range Test (DMRT). The results showed that soaking in NaCl solution had an effect on Ca oxalate content of each treatment but did not affect on the number and size of crystals Ca-oxalate and amylum size. The best treatment was found in the treatment of P2 (10% NaCl) which can reduce Ca oxalate to 22.89% with oxalate content of 78.92 ppm. The higher concentration of NaCl in the solution increasingly affect the reduction of oxalate content on purple yam. . Keywords: Amylum, Ca oxalate, Dioscorea alata L., Purple yam.